Eating patterns and food systems: critical knowledge requirements for policy design and implementation - Guyomard, Hervé; Darcy-Vrillon, Béatrice; Esnouf C; Marin, M.; Momot A; Russel, Marie; Guillou, Marion (Springer, 2012)
Eating patterns are important for building sustainable food and agricultural systems. This paper begins by presenting the main features of eating patterns worldwide. These eating patterns include the relative convergence of diets, more rapid food transition in emerging and developing countries, development of a more complex food chain, and substantial food losses and waste at distribution and final consumption stages. These patterns have negative consequences on health and the environment. The drivers of these patterns are examined to identify knowledge gaps, the filling of which should facilitate the design and implementation of actions and policies aimed at making food systems more sustainable.